2009
DOI: 10.1007/s00404-009-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Onset of labour: women’s experiences and midwives’ assessments in relation to first stage duration

Abstract: The perceptions of women in labour are as important as perinatal factors in determining the duration of the first stage of labour and should be taken into account in intrapartum care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 12 publications
6
32
0
3
Order By: Relevance
“…The range of the latent phase duration in the present study is also in line with Gross et al's observational study that women, regardless of parity, had a first stage of labor ranging between 48 minutes and 9.6 days. More research is needed about the latent phase and the classifications traditionally set by Friedman and the Swedish classification code as used in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The range of the latent phase duration in the present study is also in line with Gross et al's observational study that women, regardless of parity, had a first stage of labor ranging between 48 minutes and 9.6 days. More research is needed about the latent phase and the classifications traditionally set by Friedman and the Swedish classification code as used in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…More research is needed about the latent phase and the classifications traditionally set by Friedman and the Swedish classification code as used in the present study. Gross et al compared women's own description with midwives' diagnosed onset and concluded that irregular pain, watery fluid loss, and time between onset described by women and professionals were associated with the duration of the first stage. Therefore, the authors suggested that women's own perceptions of labor onset should be considered when determining the length of the first stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of labour onset usually involves the assessment of contraction pattern and cervical dilatation [41]. However, this evaluation can conflict with women’s own perceptions regarding the onset of their labour [42, 43], causing distress [4448]. Contradictory perceptions of progress can also occur during the expulsive phase of labour when women experience an uncontrollable urge to push [49].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly the timing of self‐diagnosis of the onset of labor varies greatly among women, and also differs from the midwives' assessments. Our research team has shown that nulliparas who identify sleep alterations as the first sign of labor perceive that their labor started an average of 11.5 hours earlier than the midwife's assessment (10). In contrast, women whose labor started with watery fluid loss or contractions had greater congruence with the midwife's assessment.…”
Section: “Listening To Women's Self‐diagnosis Of Labor Onset”mentioning
confidence: 96%